Jawabanmu

Jawaban paling cerdas!
2014-05-14T17:33:22+07:00
L i m  √(2x + 1) - 3 =  l i m √(2x/x + 1/x) - 3/x^1/2
x⇒∞  √(x - 2) - √2     x⇒∞ √(x/x - 2/x) - √2/x^1/2
                             = l i m √(2 + 1/x) - 3/√x
                               x⇒∞  √(1 - 2/x) - √2/√x
                             = √(2 + 1/∞) - 3/√∞
                                 √(1 - 2/∞) - √2/∞    (jika suatu bilangan dibagi ∞ maka nilainya 0
                             = √2/√1
                             = √2/1
                             = √2
1 5 1